2022
DOI: 10.1038/s41598-022-14814-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vivo bacteriostatic application of PPDO-coated Ag loading TiO2 nanoparticles

Abstract: Implant-associated infections limit the clinical application of implants therapy; hence, exploiting strategies to prevent biomaterial-associated infections has become important. Therefore, in this study, a series of poly (p-dioxanone) (PPDO)-coated Ag loading TiO2 nanoparticles (Ag@TiO2-PPDO) was synthesized to be applied as bacteriostatic coating materials that could be easily dispersed in organic solvent and coated onto implantable devices via temperate methods such as electrospraying. The lattice parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…As seen in Figure 4 B, all the samples showed quite similar peaks at 2 θ of 21.8° and 23.5°. PPDO exhibited the characteristic diffraction peaks at 2 θ of 21.9° and 23.7°, which attribute to the reflection of (210) and (020) [ 25 , 26 ], while PCL shows two characteristic peaks at 2 θ of 21.2° and 23.5°, which correspond to the (110) and (200) crystallographic planes of the PCL crystalline structure [ 18 ]. Therefore, the diffraction peaks for all the samples in this work should be the mixture of the characteristic peaks of PPDO and PCL domains.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figure 4 B, all the samples showed quite similar peaks at 2 θ of 21.8° and 23.5°. PPDO exhibited the characteristic diffraction peaks at 2 θ of 21.9° and 23.7°, which attribute to the reflection of (210) and (020) [ 25 , 26 ], while PCL shows two characteristic peaks at 2 θ of 21.2° and 23.5°, which correspond to the (110) and (200) crystallographic planes of the PCL crystalline structure [ 18 ]. Therefore, the diffraction peaks for all the samples in this work should be the mixture of the characteristic peaks of PPDO and PCL domains.…”
Section: Resultsmentioning
confidence: 99%
“…Hexafluoroisopropanol was purchased from Innochem (Beijing, China). NPs of 12%Ag@TiO 2 -PPDO and 16%Ag@TiO 2 -PPDO were synthesized as reported in our previous work [ 11 ]. Xenon lamp equipped with UVCut 420 optical filter, which could filter out light below 420 nm was purchased from China education Au-light (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous jobs, a kind of poly( p -dioxanone) (PPDO) grafted Ag-incorporated TiO 2 nanoparticles (Ag@TiO 2 -PPDO NP) has been successfully synthesized. Ag@TiO 2 -PPDO NP could inhibit the proliferation of Staphylococcus aureus [ 11 ]. Spectroscopic studies have shown that Ag@TiO 2 -PPDO NP could respond to visible light, which might make Ag@TiO 2 -PPDO NP inhibit the proliferation of bacteria continually and positively with irradiation of visible light.…”
Section: Introductionmentioning
confidence: 99%